THE CASE OF SEINE NET FISHING GEAR TECHNOLOGY IN KORONG TOBOH KANAGARIAN CAMPAGO V KOTO KAMPUNG DALAM VILLAGE, PADANG PARIAMAN DISTRICT, WEST SUMATRA PROVINCE. - Febriantoni, Penny; Yani, Alit Hindri; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACT.This research was conducted on Sepember 2014 in Korong Toboh Kanagarian Campago V Koto Kampung Dalam Village, Padang Pariaman District, West Sumatra Province. The purpose of this study was to determined the common construction of technical aspect and the operation, to know the friendly environmental level and to know the feasibllity effort of seine net.This research used a survey method. The aggregation of forms by taking the unit sample of seine net in puposive that is the sample of the common boat size from the able population, which is saw by the boat size, fishing gear and the instrumental of fishing gear that is used in Korong Toboh Kanagarian Campago, V Koto Kampung Dalam Village, Padang Pariaman District, West Sumatra Province.The analyze of forms used the analyze of friendly environmental of fishing gear technology that’s suitable to FAO criteria, rentability analyze and the feasibllity effort.From the result of the analyze friendly environmental technology showed that this fishing gear within to the friendly environmental fishing gear with the point is 26,22, it is means that this seine net is suitable to a friendly environmental fishing gear.Keyword: Seine net, friendly environmental, feasibility effort, West Sumatera.